Household income and nutrient adequacy in women of reproductive age: A study in Babakan Village, Indonesia - Ana Dina Resa; Nailan Faza Prasetyaji Fidela (BIO Web of Conferences)
Background: The condition of Chronic Energy Deficiency and anemia often occurs in women of reproductive age and can lead to health problems. Objective: This research aims to examine the relationship between household income and the adequacy of energy, protein, and iron levels in women of reproductive age in Babakan Village. Methods: The research employs a cross-sectional design. The respondents are 78 women of reproductive age, residing in Babakan Village, determined using purposive sampling. The instruments in this research include interview questionnaires (household and characteristics) and 1x24-hour food recall forms (levels of energy, protein, and iron adequacy). Hypothesis testing in this research uses the Spearman test to determine the relationship between household income and the adequacy of energy, protein, and iron levels. Results: The research results indicate a significant relationship between income and iron adequacy with a value of p < 0.05, while there is no significant relationship between income, energy, and protein adequacy with a value of p > 0.05. Conclusion: This study indicates that higher income may improve access to nutritious foods but does not ensure better nutrient adequacy in this population.